Technology for Organizing Trips to Historical Sites Outside the Audience - Gulbakhor Azamovna Ismoilova (Research Parks Publishing LLC, 2021)
The article deals with the formation of ecological culture in students, the reflection of issues of ecology and nature protection, its historical development processes and future prospects. In today's world, where the promotion of environmental culture in our country is becoming an integral part of public policy as an important task, it is of great importance. We aimed to study the process of using non-traditional methods in the development of ecological culture of students through the teaching of the history of Uzbekistan and its technology. Education, on the other hand, is a great impetus for the formation and development of culture. In today's world, where the promotion of environmental culture in our country is becoming an integral part of public policy as an important task, it is of great importance